Trade Costs, FDI incentives, and the Intensity of Price Competition - Giuseppe Francesco Gori; Luca Lambertini; Alessandro Tampieri (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2012)
Empirical evidence shows that an increase in trade liberalisation causes an increase in foreign direct investments (FDIs). Here we propose an explanation to this apparent puzzle by exploiting the intensity of competition in a Bertrand duopoly with convex costs where the two firms enter in a new market. We adopt Dastidar's (1995) approach, delivering a continuum of Bertrand-Nash equilibria ranging above marginal cost pricing, to show that softening competition may indeed more than offset the standard effect generated by trade costs, thereby leading to a positive relationship between trade liberalisation and FDIs.
Keywords: F12; F13; F23; 330